THE EXTENT OF AVAILABILITY OF DIGITAL TRANSFORMATION REQUIREMENTS AT AL-MUSTANSIRIYAH UNIVERSITY: A CASE STUDY - Ayah Talib Jameel; Kadhim Ahmed Jawad (Academic Bright Collaboration, 2026)
This research assesses the digital transformation readiness at Al-Mustansiriyah University using a comprehensive checklist covering seven key requirements: human resources; regulations, laws and legislation; technical and digital infrastructure; organizational structures and administrative processes; information and communication systems and networks; the development of a scientific culture and internal preparedness; and local and international partnerships and cooperation. The study aims to identify strengths, weaknesses, and the extent of the digital gap. A descriptive-analytical case study approach was adopted. Data was collected via the checklist and analyzed using a three-point Likert scale (Fully Implemented, Partially Implemented, Not Implemented) to determine compliance levels. Key findings reveal an overall digital gap of 46.5% at the university. Notably, this is primarily a governance and management gap rather than a technological one; the technical and digital infrastructure is significantly more developed than the organizational, administrative, and collaborative dimensions. Consequently, the study recommends bridging this organizational gap by re-engineering the university’s administrative structure, allocating an independent budget, and fostering openness to international best practices. These steps will maximize the benefits of the existing digital infrastructure, which remains the university’s greatest asset in its digital transformation journey.